A 20 años de la Ley del Procedimiento Administrativo General - Morón Urbina, Juan Carlos (2021)
Advocatus had the opportunity to meet with two Peruvian lawyers of great experience in the administrative law field so that they couldshare their reflections on the Peruvian General Administrative Procedure Law —LPAG, 20 years after its enactment.